2017
DOI: 10.1038/s41598-017-01167-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling defines the impact of electronic cigarettes on human airway epithelial cells

Abstract: While all forms of tobacco exposure have negative health effects, the significance of exposure to electronic cigarettes (eCig) is not fully understood. Here, we studied the global effects of eCig on the micro RNA (miRNA) transcriptome in human lung epithelial cells. Primary human bronchial epithelial (NHBE) cells differentiated at air-liquid interface were exposed to eCig liquid. Exposure of NHBE to any eCig liquid resulted in the induction of oxidative stress-response genes including GCLM, GCLC, GPX2, NQO1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 76 publications
(100 reference statements)
0
34
1
Order By: Relevance
“…Various pathways such as the phospholipid and fatty acid triacylglycerol metabolisms were significantly enriched after ECIG-exposure [24]. Another study investigated the micro RNA (miRNA) response and the exposure of differentiated airway epithelial cells with ECIG-vapor resulted in the upregulation of oxaidative stress genes [58]. ECIGs also modify the metabolome of epithelial cells and showing significant changes partially overlapping with the effect of TCIG [59].…”
Section: Resultsmentioning
confidence: 99%
“…Various pathways such as the phospholipid and fatty acid triacylglycerol metabolisms were significantly enriched after ECIG-exposure [24]. Another study investigated the micro RNA (miRNA) response and the exposure of differentiated airway epithelial cells with ECIG-vapor resulted in the upregulation of oxaidative stress genes [58]. ECIGs also modify the metabolome of epithelial cells and showing significant changes partially overlapping with the effect of TCIG [59].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence from previous studies that ECV has the potential to induce oxidative stress in airway cells. For example, GOEL et al [23] reported that ECV contains up to 10×10 13 free radicals per puff [23], CARNEVALE et al [24] reported increased circulating oxidative stress markers in adults after vaping, and SOLLETI et al [25] reported that ECV is a potent inducer of oxidative stress response genes in bronchial epithelial cells in vitro. In the present study, the high OP of ECV, the presence in ECV of redox-promoting metals such as copper and iron, and attenuation of ECV-stimulated pneumococcal adhesion by the antioxidant N-acetyl cysteine, supports a role for oxidative stress as the initial stimulus for PAFR-dependent adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Solleti et al demonstrated that smoking of electronic cigarettes affected the expression of 125 miRNAs (26). The present study systematically analyzed the expression patterns of miRNAs in nicotinetreated PDLCs.…”
Section: Discussionmentioning
confidence: 90%